Successful Treatment with Radioiodine for Antithyroid Drug-Induced Agranulocytosis in Graves' Disease (Bangladesh Journal of Nuclear Medicine, 2023)
Background: Graves’ disease (GD) is an autoimmune disorder and the leading cause of hyperthyroidism. Antithyroid drugs (ATDs) are available treatment option. Agranulocytosis is a rare but potentially fatal complication of ATD in hyperthyroidism management. The study's objectives include clinical symptoms of ATD-induced agranulocytosis in Graves' illness and the difficulties in clinical care in addition to radioactive iodine therapy (RAIT).Methods: Twelve patients with ATD induced agranulocytosis referred to NINMAS between 2021to 2022 for RAIT therapy were included in this study. All the patients with hyperthyroidism and agranulocytosis or leukopenia were taken in this study.Results: The age of the 12 patients (female: male = 10:3) was 26 to 56 years (mean SD: 38.41±13.9 years). Among the twelve patients 10 were treated with carbimazole and two with PTU for Graves’ disease. Initial dose of ATD was 15-30 mg daily. The most common clinical manifestations were fever (100%), sore throat (41.6%), oral ulcer (16%), rash (41.66%), loose motion (16.66%) and atrial fibrillation (8.33%) with deep vein thrombosis (DVT). Agranulocytosis developed between 7th and 547th days after initiation of ATD; all of them developed early onset except one who developed agranulocytosis after 1.5 years of initiation of ATD. All 12 patients were treated immediately after diagnosis of agranulocytosis following prompt discontinuation of ATD, they were treated with antibiotic with 12 cases, G CSF in one case, KI in one case, glucocorticoid in two cases, and beta blocker in all cases. After intensive and supportive treatment in hospital, all the patients recovered with absolute neutrophil counts of more than 500/mm3 in 5 to 15 days (mean SD: 7.6 3.4 days). Nine patients were treated with lithium carbonate supplement to reduce FT3 level. Average dose of lithium carbonate was 600 mg. After that patients were referred for RAIT. TRAb were positive in seven patients and average were 4.2 U/L. Plasmapheresis was done in three patients and one patient in two times due to high FT4 level before RAIT. Lithium carbonate supplementation reduce thyroid hormone level but not to the optimum level. All the 12 patients were treated with RAIT. Average dose RAI 10.9 mCi, average follow up period 2.3 years. Two patients required second dose of RAIT due to persistent hyperthyroidism. Six patients became hypothyroid, two were in hyperthyroid state (on plan for second therapy), four patients are euthyroid at present and they are on follow up. No fatal condition was found in this study.Conclusion: The most cost-effective method of managing agranulocytosis induced by thionamide-derived ATD is that all patients with thyrotoxicosis must be informed that their white blood cells and differential counts should be checked immediately whenever the “common cold” symptoms occur during treatment, especially within the first three months of medication. Contraindication to ATDs; RAI is a safe and effective alternative.Bangladesh J. Nuclear Med. 26(1): 39-43, 2023